How time-varying elasticities of demand translate into the excise-related laffer surface - Olesiński, Bartosz; Rozkrut, Marek; Torój, Andrzej (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2020)
In an environment of growing real prices and changing consumption patterns in the tobacco market, the question arises whether the price elasticities of demand may be estimated as constant parameters over multi-annual samples. The authors develop a methodological framework for estimating time-varying demand elasticities in a state-space model, estimated via maximum likelihood based on the Kalman filter. This model is applied to evaluate various, alternative paths of tobacco excise tax rates. Importantly, both in estimation and in simulations, the authors account not only for changes in the level, but also in the structure of excise tax by exploring the market segmentation into a lower and a higher end of the market. This allows the authors to contribute to the existing literature about the optimum structuring of the tax between the specific and ad valorem rates and to analyse the Laffer surface (rather than a curve). The measurement results indicate some growth in the magnitude of price elasticity of demand since 2005, and the simulations show that the differences between the actual and the optimum taxation policy for tobacco products were marginal in the 2014-2018 period
Argumenta Oeconomica, 2020, Nr 1 (44), s. 257-299